Coupled nitrification and N2 gas production as a cryptic process in oxic riverbeds - Liao Ouyang (Nature Portfolio, 2021)
The N cycle involves complex, microbially-mediated shuttling between ammonium, nitrite and nitrate, with climatically important greenhouse gas byproducts. Here the authors use isotope labeling experiments in river sediments and find a cryptic new step in the N cycle between nitrification and the removal of fixed N through N2 gas production.